Respostas

A melhor resposta!
2014-04-26T07:17:22-03:00
A) Para que a função tenha raízes idênticas, Δ = 0

Portanto, K = 5/4

y = ax² + bx + c

f(x) = x² - 3x + K + 1

a = 1
b = -3
c = K + 1

b² - 4ac = 0
(-3)² - 4.1(K + 1) = 0
9 - 4 (K +1) = 0
9 - 4K - 4 = 0
5 = 4K
K = 5/4

Verificação:

c = K + 1
c = 5/4 + 1
c = 5/4 + 4/4
c = 9/4

f(x) = x² - 3x + 9/4

a = 1
b = -3
c = 9/4

Δ = b² - 4ac
Δ = (-3)² - 4(1)(9/4)
Δ = 9 - 36/4
Δ = 9 - 9
Δ = 0
x = -b +- √Δ / 2a

x1 = x2

x = 3 +- 0 / 2
x = 3/2

---------------------------------------------------------------------------------------------------------------------------

b) Para que a função tenha duas raízes distintas, Δ ≠ 0

Portanto, K ≠ 5/4

b² - 4ac ≠ 0
(-3)² - 4.1(K + 1) ≠ 0
9 - 4 (K +1) ≠ 0
9 - 4K - 4 ≠ 0
5 ≠ 4K
K ≠ 5/4


2 3 2